Ultra-Micro Lending Eligibility Support System With Exponential Comparison Method (MPE) - Ninuk Wiliani; Mulyana Adi Supatra; Herry Wahyono (Jurnal Riset Informatika, 2023)
The process of providing credit can now be done quickly and closely through the presence of BRILink agents with additional facilities in addition to payment points, namely as partners of ultra-micro loans, which are now popularly called UMi Partners, where BRILink agents can distribute microloans with a loan range of 1 to 5 million. This is done by management as a financial inclusion program and as a revitalization of work in all operational work units (UKO). This research uses the Exponential Comparison Method (MPE) to determine credit granting decisions to optimize all existing information systems by implementing a system that can be used and run by UMi partners to improve the process of providing creditworthiness to their partners. The results of the calculations carried out by the system are manual calculations that have been carried out so that the results of this study can be applied correctly to produce creditworthiness that helps the credit-granting process.